ALTERNATIF PENYELESAIAN SENGKETA (APS) - Arisma Damayanti; Firdatul Halimah; Reva Khoirotul Ramadhani; Tabita Vasya Nurin N; Ulfa Khusnul Ambarwati; Zami Salsabela (Jurnal Ekshis, 2025)
Humans, as social beings, are often involved in legal relationships that may lead to disputes. To resolve such conflicts peacefully, Alternative Dispute Resolution (ADR) offers a non-litigation solution that is more efficient and cooperative. In Indonesia, although peaceful settlement has existed within traditional practices, the development of ADR has progressed more rapidly in Western countries. This study employs a descriptive qualitative approach through literature review to examine ADR mechanisms in resolving contractual disputes. Such disputes arise from violations of contractual rights and obligations, and may be resolved through litigation or alternative methods such as mediation and arbitration. A case study on a land sale agreement illustrates that a party who has not received full payment is entitled to withhold their obligations, in accordance with the principle of exceptio non adimpleti contractus. This research also highlights the importance of strengthening ADR education in universities to prepare legal practitioners capable of handling disputes outside of court